1982
DOI: 10.1182/blood.v60.4.959.959
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy and percentage of S-phase cells determined by flow cytometry correlate with cell phenotype in childhood acute leukemia

Abstract: Cellular DNA content distributions of propidium-iodide-stained bone marrow blasts were determined by flow cytometry (FCM) for 225 untreated children with acute leukemia and were correlated with leukemia cell phenotype and karyotype. Aneuploidy of the primary malignant stem line was detected in 54 cases (24%): 51 hyperdiploid and 3 hypodiploid. A second stem line with approximately twice the DNA content of the primary stem line was recognized by FCM in 28 cases (23 ALL, 5 ANLL) and may be an important source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(23 citation statements)
references
References 24 publications
2
18
0
3
Order By: Relevance
“…We found that the mean PCNA expression is significantly higher in T-ALL than in non-T-ALL, in line with the similar finding of Keim et al (1990). Nevertheless, one should bear in mind that both our series and Keim's did not contain mature B-ALL, known to have a very high proliferation activity (Look et al, 1982;Ffrench et al, 1987). The conclusion which could be drawn from this observation is that T-ALL cells divide more intensively than other immunological types (except mature B), in terms, for example, of the shortening of the duration of all cell-cycle phases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the mean PCNA expression is significantly higher in T-ALL than in non-T-ALL, in line with the similar finding of Keim et al (1990). Nevertheless, one should bear in mind that both our series and Keim's did not contain mature B-ALL, known to have a very high proliferation activity (Look et al, 1982;Ffrench et al, 1987). The conclusion which could be drawn from this observation is that T-ALL cells divide more intensively than other immunological types (except mature B), in terms, for example, of the shortening of the duration of all cell-cycle phases.…”
Section: Discussionsupporting
confidence: 89%
“…When all T-lineage ALL cases are considered as one group, no difference was found for S or S+G2+M cells between T-cell lineage and B-cell (mature B-cell excluded) ALL (Ffrench et al, 1987). However, the percentage of bone marrow S-phase ALL blasts, determined as the 3 H-thymidine labelling index (Murphy et al, 1977;Dow et al 1982) or flow cytometry (Look et al, 1982) was higher in E(+) T-cell ALL when compared not only to B-lineage ALL (mature B-ALL excluded), but also to E(ÿ) T-lineage ALL. In order to study ALL blast proliferation status more precisely, we used PCNA and certain cdks and cyclins expression at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey adds a cautionary note to those seeking to predict survival of adults with ALL on DNA index alone. DNA index provides only a measure of ploidy without detailed knowledge of the more prognostically important structural change (Look et al, 1982;Smets et al, 1987). The hierarchical classification was more prognostically significant than the ploidy classification used alone, and only the hierarchical classification added prognostic significance to age, sex and WBC.…”
Section: Discussionmentioning
confidence: 99%
“…By the 1970s the hyperdiploid (HD) pre-B pediatric acute lymphoblastic leukemia (B-pALL), and by the mid 1980s even the high hyperdiploid (HeH) category was defined using conventional cytogenetic analysis (CCA) as well as DNA cytometry [1][2][3][4][5][6][7][8][9][10]. Later, based on treatment response, the low hyperdiploid (HeL) with modal number (MN) 47-50 and high hyperdiploid (MN 51-67) subgroups were distinguished, the latter of which is the most frequent (25-30%) subtype of B-pALL [11][12][13].…”
Section: Introductionmentioning
confidence: 99%